2020
DOI: 10.1017/s0033291719003908
|View full text |Cite
|
Sign up to set email alerts
|

Much more than just shyness: the impact of social anxiety disorder on educational performance across the lifespan

Abstract: Background. Social anxiety disorder (SAD) has been linked to academic underachievement, but previous studies had methodological limitations. We investigated the association between SAD and objective indicators of educational performance, controlling for a number of covariates and unmeasured confounders shared between siblings. Methods. This population-based birth cohort study included 2 238 837 individuals born in Sweden between 1973 and 1997, followed-up until 2013. Within the cohort, 15 755 individuals had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
41
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 42 publications
5
41
0
7
Order By: Relevance
“…Unfortunately, social anxiety disorder affects self-concept and individual performance directly and long-term [ 15 , 16 ]. Therefore, timely diagnosis and intervention are necessary for those affected by social anxiety disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, social anxiety disorder affects self-concept and individual performance directly and long-term [ 15 , 16 ]. Therefore, timely diagnosis and intervention are necessary for those affected by social anxiety disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Such symptoms are common and typically first occur in early adolescence [ 8 ], and although some studies have observed that social anxiety symptoms are associated with reduced educational achievement (e.g. [ 9 ]), the mechanisms by which they interfere with young peoples’ learning abilities are unclear. It has been suggested that concentration may be one such mechanism [ 10 ]: concentration is a predictor of educational achievement [ 11 ] and social anxiety symptoms are associated with reduced concentration [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social anxiety disorder (SAD) is highly prevalent and it's the most common anxiety disorder among all types of anxiety disorders and the third most common psychiatric condition after major depression and alcohol dependence. [ 1 ] Social anxiety disorder (SAD) is characterized by persistent fear/anxiety about one or more social or performance situations in social settings. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%